The Practices of Political Patronage and Clientelism of the Democrat Party in the 2014 Legislative Election in Ponorogo Regency - FIKRI, HAIDAR (Universitas Muhammadiyah Yogyakarta, 2017)
The Democrat Party in Ponorogo Regency still exists despite cases of corruption that ensnared some national political actors. The Ponorogo Regency attracted the attention of many parties and candidates, including that of the Democratic Party, during the legislative elections in 2014. This concern included candidate efforts to transform the party through the provision of patronage material in diverse forms such as a unique distribution process, and a variety of patronage models. This research was conducted to determine the practice of patronage politics of the Democrat Party in the Ponorogo Regency in 2014. The theory used for this research on the practice of patronage is the theory of patronage and clientelism according to the variables offered by James Scott. The qualitative research methods are data collection interviews, and documentation and re- ports related to the elections in Ponorogo. The results of this study suggest that the practice of patronage in Ponorogo conducted by the Democrat’s candidate is very diverse, ranging from the use of money given to voters, the provision of public goods targeting social groups such as farmers and youth organizations on the assumption that they were impressionable on an emotional level, and giving pork barrels in the form of road construction and irrigation disbursed through the BKAD (Inter-agency Cooperation Board). Patronage is certainly dis- tributed through clientelism networks such as successful teams that have been prepared since before the election, a network of social groups that utilize a warok, considered a person who has a wise and exalted nature and takes advantage of the village elite. This is a political machine that runs a network to help distribute patronage so that it becomes clientelistic. The interest of this study is the associa- tion between patronage and clientelism that is fused with the local culture of the Ponorogo community and was mobilized in the legislative election in 2014.